Strategi Pembelajaran Sosial Emosional (SEL) untuk Mengatasi Perundungan Siswa Kelas 5 Sekolah Dasar - Magfirah Magfirah; Daroe Iswatiningsih (Lembag, 2025)
Bullying is one of the prominent social problems that significantly impacts the psychological well-being and academic development of elementary school students. This study aims to explore the implementation of Social-Emotional Learning (SEL) strategies in addressing bullying behavior among fifth-grade students at SD Inpres Pannujuang, located in Bajeng Barat District, Gowa Regency, South Sulawesi. Employing a qualitative approach with a case study method, data were collected through classroom observations, semi-structured interviews, and document analysis. The findings reveal that the integration of SEL strategies such as fostering self-awareness, managing emotions, enhancing social skills, and encouraging responsible decision-making effectively reduces the frequency and intensity of bullying while promoting healthier peer relationships. Incorporating SEL into daily learning practices fosters a safer, more inclusive, and supportive classroom climate. This study concludes that SEL can be systematically embedded into classroom instruction and teacher professional development as a preventive approach to bullying in elementary schools.